Gabriel Zaid, Essayist - Gomes, Miguel (Anales de Literatura Hispanoamericana, 2010)
This article examines the unifying ideological and formal elements underlying Gabriel Zaid’s oeuvre. It focuses on three main aspects of his poetics: (1) His peculiar dialectics, which allows him to redefine culture’s realm through a phenomenology of book-reading in the cyberspace era; (2) the tense relations between a writer’s social endeavors and his aesthetics, especially in postcolonial traditions such as those of Spanish-America, with strict expectations about the civic role of intellectuals; and (3) Zaid’s theory of genres and the place the essay and poetry have in it.
Keywords: Essay; Spanish-American Essay; Mexican Essay; Genre Theory; Culture; Reading